Is it possible to achieve bio‐equivalence between an oral solid immediate‐release and an analogue enteric‐coated formulation?. (27th July 2016) - Licht, Dannit; Cohen, Rachel; Spiegelstein, Ofer; Rabinovich‐Guilatt, Laura; Zholkovsky, Marina; Gilbert, Adrian; Dressman, Jennifer B.; Safadi, Muhammad
Abstract: Objectives: While bioequivalence between enteric‐coated and immediate‐release formulations can be achieved in terms of AUC, gastric emptying of enteric‐coated dosage forms is a stochastic event, usually leading to lower C max values than those observed with the corresponding immediate release. This article examines challenges of developing enteric‐coated dosage forms which are bioequivalent to the corresponding immediate‐release formulations in terms of both AUC and C max using rasagiline as a model compound. Methods: In vitro drug release profiles of enteric‐coated formulations were obtained and compared to those of the immediate‐release formulation by dissolution testing. Pharmacokinetics was evaluated in bioequivalence studies in healthy human volunteers after single oral administration of enteric‐coated and immediate‐release formulations. Key findings: The initial enteric‐coated pellet formulation prototype was equivalent in terms of AUC, but differed in C max ; a second formulation prototype, consisting of a single‐unit core and enteric‐coating film, proved to be bioequivalent to immediate‐release rasagiline tablets in terms of AUC and C max . In vitro, it released rasagiline rapidly at a pH of 6.8. Conclusions: Despite differences in gastric emptying between disintegrating immediate‐release and enteric‐coated solid dosage forms, bioequivalence in pharmacokinetic studies was achieved.